(untitled) (Global Journal of Medical Research, 2019)
The paper studied metabolic syndrome in the structure of victims with broken limbs. Analyzed the results of examination and surgical treatment of 202 patients with fractures of the limbs on the background of metabolic syndrome. Developed a multidisciplinary approach involving cardiologist, endocrinologist, anaesthetist and expert in resuscitation for planning surgical intervention can reduce intra and postoperative complications.